Analysis of green deal communication on twitter: environmental and political perspective - Balcarova, Tereza; Pilarova, Lucie; Prokop, Michal; Jadrna, Monika; Kvasnickova Stanislavska, Lucie; Pilar, Ladislav (Frontiers in Environmental Science, 2024)
The Green Deal and its implementation are generating discussions across society. Changes brought about by the agreement could impact sustainable development worldwide; therefore, identifying the most common Green Deal-related topics on a global scale can offer insight into the public mood around implementation of the agreement. Social networks provide the opportunity to find such topics because they contain a large amount of data produced by users worldwide: analysis of their content can therefore provide insight into the discourse on the Green Deal and identify the sentiment in discussions around this topic. In this article, we present perceptions of the Green Deal and identify the main Green Deal-related topics based on analysis of communication on the Twitter social network (currently X social network). Using the search terms “green deal,” “greendeal,” and “#greendeal,” 192,567 tweets from 89,328 unique users were captured between 1 January 2019 and 31 March 2023. We identified the 40 most used unique hashtags that people used when communicating about the Green Deal, which included “#EU,” “#eugreendeal,” and “#climatechange,” and the 16 most relevant topics discussed in relation to the Green Deal, which included both European (“European Green Deal”) and North American (“Green New Deal”) perspectives. Each topic was associated with a certain amount of negative, positive, or neutral sentiment: the most positive sentiment was associated with the “Industrial plan” and “Hydrogen” topics, and the most negative sentiment was associated with topics relating to “Joe Biden” and “Alexandria Ocasio-Cortez.” Overall, our analysis of the discourse regarding the Green Deal offers organizations and decision-makers insight into how people perceive different aspects of the Green Deal and related topics. This may be beneficial in tackling disinformation across social networks and increasing public awareness, which could create a society better equipped to face the global concern of climate change.